Pelatihan Pengolahan Limbah Kulit Udang Menjadi Kaldu Bubuk Pada UMKM Pempek Lela di Desa Sungsang - Ira Gusti Riani; Eka Nurriza Khairunnisa; Raudhatus Sa’adah; Aldilla Sari Utami; Madyasta Anggana Rarassari; Nia Boru Ritonga; Yulia Hapsari (Universitas Muhammadiyah Palembang, 2024)
Sungsang Village is located in the coastal area of the East Coast of Sumatra. The people of Sungsang village are also the same as people living in other coastal areas, namely they have diverse livelihoods. One of the livelihoods of the breech community is the business of making shrimp pempek where there is a problem in the form of shrimp skin which becomes waste from making pempek and has not been utilized so that it becomes one of the causes of environmental pollution, therefore it is important to provide knowledge to pempek entrepreneurs and housewives to be able to process the waste by making shrimp skin into powdered broth that can be sold or used at home. The method of service carried out is by providing direct practice. After the service, business actors and housewives in Sungsang 4 village gained new knowledge to process waste into valuable products. The enthusiasm and participation of women in the shrimp pempek business and housewives was very high when participating in training on making powdered broth made from shrimp skin waste in Sungsang Village 4.